Novel mobile device-based tool to document sideline evaluation of athletes - Apple, R. P.; Karpinos, A. R.; Bellamy, D. M. (Current Sports Medicine Reports, 2019)
We describe the implementation of the Athletic Injury Database (AID), a mobile device-based tool for documenting sideline encounters with athletes. Primary measures of the implementation process were: 1) patterns of AID use, 2) nature of sideline encounters captured, and 3) providers` reported satisfaction. Over 2 yr, the AID captured 6237 sideline encounters by athletic trainers and physicians. Most encounters were among athletes participating in football (51%), soccer (15%), and basketball (12%). Knee and ankle injuries were most common. A total of 77% of sports medicine providers were satisfied with the AID. Providers can use information gleaned from a tool like the AID to improve documentation of care provided to athletes.